AIDS in Europe : new challenges for the social sciences - Moatti, J.-P. (Jean-Paul) (Social aspects of AIDS., 2000)
AIDS in Europe provides a comprehensive overview of current social and behavioural research on HIV and AIDS for all health professionals.